2010
DOI: 10.1016/j.bbrc.2010.04.125
|View full text |Cite
|
Sign up to set email alerts
|

DHEA attenuates PDGF-induced phenotypic proliferation of vascular smooth muscle A7r5 cells through redox regulation

Abstract: It is known that dehydroepiandrosterone (DHEA) inhibits a phenotypic switch in vascular smooth muscle cells (VSMC) induced by platelet derived growth factor (PDGF)-BB. However, the mechanism behind the effect of DHEA on VSMC is not clear. Previously we reported that low molecular weight-protein tyrosine phosphatase (LMW-PTP) dephosphorylates PDGF receptor (PDGFR)-β via a redox-dependent mechanism involving glutathione (GSH)/glutaredoxin (GRX)1.Here we demonstrate that the redox regulation of PDGFR-β is involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
1
3
1
1
Order By: Relevance
“…For Glrx and Cx3cl1, up- and downregulation, respectively, were even confirmed with RT-PCR. Contrary to our results, where upregulation of Glrx was associated with increased proliferation of A7r5 VSMCs, upregulation of Glrx has been linked to decreased proliferation of A7r5 VSMCs, as reported by Urata et al [128]. In pulmonary artery SMCs and in human lung cancer tissue, Glrx expression showed an inverse correlation with proliferation [129, 130].…”
Section: Discussioncontrasting
confidence: 95%
“…For Glrx and Cx3cl1, up- and downregulation, respectively, were even confirmed with RT-PCR. Contrary to our results, where upregulation of Glrx was associated with increased proliferation of A7r5 VSMCs, upregulation of Glrx has been linked to decreased proliferation of A7r5 VSMCs, as reported by Urata et al [128]. In pulmonary artery SMCs and in human lung cancer tissue, Glrx expression showed an inverse correlation with proliferation [129, 130].…”
Section: Discussioncontrasting
confidence: 95%
“…These results were confirmed in vivo by a decrease of vascular remodeling in the rat model of ballooninjured carotid treated with DHEA, showing the potential of DHEA as therapeutic for restenosis. It was demonstrated that PDGF-induced proliferation is inhibited by DHEA through a GSH/GRX1 mechanism [75], GRX1 playing an important role in PDGF signal regulation by a downregulation of tyrosine phosphorylation of the PDGF receptor [76]. This is in agreement with previous findings showing that GRX1 and γ-Glutamylcysteine synthetase (γ-GCS) display a PPAR response element in their promoter and are up-regulated at the transcriptional level by PPARα.…”
Section: Dhea Anti-proliferative Propertiessupporting
confidence: 89%
“…We used rat A7r5 cells for this study [17]. The cells were cultured in DMEM supplemented with 10% FBS at 37°C under a humidified atmosphere of 5% CO 2 .…”
Section: Cell Culture and Gamma-ray Irradiationmentioning
confidence: 99%